Asuhan Keperawatan pada Klien Ny. “S” dengan Demam Berdarah Dengue di Ruang Perawatanbaji Nyawa RSUD Labuang Baji Makassar - Tuty Alawiyah Alimuddin; Amiruddin J (PPNI UNIMMAN, 2023)
Dengue hemorrhagic fever is an infection caused by the Dengue virus which is transmitted by the aedes aegypti mosquito which has most frekuently occurred in humans in recent years, so it is still a world health problem. The aim of this research is to gain knowledge about what Dengue fever is and its cause, gained truly real experience in implementing nursing care for the clien Mrs “S” with Dengue hemorrhagic fever in the baji life room at Labuang Baji Hospital, Makassar for 3 days starting from 18-20 April 2023. Collected techniquest Data was collected using interview techniquest, Observation and physical examination. The result of this examination were an assessment of heartburn, the patien stated that the paint felt like a stabbing sensation,the pain was felt when the patient moved, and the pain was reduced when the patient changed a half-sitting position or performed deep breathing relaxation techniques and grimaced facial expression. The patient said the pain he felt usually lasted 1-3 minutes, the patient said the pain scale was 3. In nursing diagnoses there are 3 diagnoses found in real cases, namely acute pain related to biological agents,nutritional imbalance less than the body’s needs related to lack of appetite,self-care devicits are related to weakness and fatigue. In implementing the action plan for Mrs “S” patients with cases of Dengue fever refers to nursing problems in patients by paying attention to the patient’s condition. Nursing implementation for Mrs”S” is adjusted to am action plan that has been determined so that the nursing problems faced by the patient are quickly resolved or prevented.After carrying out nursing care for the three diagnoses, all diagnoses are resolved.